Prevalence, risk and resilience factors of mental health conditions among female sex workers: a systematic review and meta-analysis - Kalinowski, Olivia; Lotysh, Anastasiia; Kaya, Gizem; Kroehn-Liedtke, Franziska; Zerbe, Lena Karoline; Mihaylova, Hristiana; Sipos, Krisztina; Rössler, Wulf; Schouler-Ocak, Meryam (Frontiers in Public Health, 2025)
IntroductionFemale sex workers are a vulnerable hard-to-reach group. Research in this field is scarce due to several issues, such as methodological difficulties or societal stigmatization. Most of the available literature focuses on sexually transmittable diseases. This review and meta-analysis aim to compile literature on the mental health of female sex workers. We investigated the prevalence of as well as risk factors for mental disease among female sex workers globally.MethodsUtilizing Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted a comprehensive search across several databases, ultimately analyzing data from 80 studies comprising 24,675 individuals in total.ResultsMost of the studies stemmed from the United States (n = 24), followed by China (n = 12), India (n = 7) and Kenya (n = 5). Four studies were conducted in South Africa and three in Mexico. Two studies originated from Australia, Cambodia, Thailand, the Netherlands, and Uganda. Single studies were identified from Scotland, Switzerland, Israel, Portugal, Mongolia, Malawi, Cameroon, Ukraine, Togo, Lebanon, the Dominican Republic, Tanzania, Puerto Rico, Ethiopia, and Moldova. The review highlights significant heterogeneity in the prevalence of mental health issues such as anxiety, depression, suicidality, post-traumatic stress disorder (PTSD), substance use and dependence, investigating the influence of socio-economic, legal, and individual factors on these outcomes. The meta-analysis reveals that while factors like legal status of sex work and economic conditions did not show any impact, specific demographic characteristics, notably female sex workers living with human immunodeficiency virus (HIV), migrant female sex workers, or female sex workers engaged in substance use, exhibit notably higher mental health challenges.DiscussionThese findings suggest the critical need for targeted mental health interventions and policy reforms that consider the complex interplay of various factors affecting sex workers. Future research should focus on under-researched regions and subgroups within this population to enhance understanding and support the development of comprehensive health services.Systematic review registrationPROSPERO, CRD42022312737, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022312737.